ANALISIS KONSUMSI ENERGI, EMISI CO2, DAN STASIUN PENGISIAN BUS LISTRIK (STUDI KASUS BUS TRANS JOGJA JALUR 3A) - , ATIKA NURUL HIDAYAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Transportation sector is the largest consumer of petroleum which consume 277 million BOE in 2012. Beside that, the increasing of energy needs compared to the availability was unbalance. Improving the quality of public transport is one step that can be done to support the changes of transportation mode from private vehicles into public transits. The provision of electric buses is a solution to overcome these problems because it will reduce the emissions and energy consumption in the city of Yogyakarta. Trans Jogja bus driving cycle is measured using GPSmap 76CSx to obtain parameters that will be used for energy consumption calculation. Energy consumption is determined by dynamic model of electric bus. After that, CO2 emissions calculated and charging system scenario is determined. Data processed into driving cycle graph with 39623 m distance, 7844 s travel time, 18.2 km/h average speed, and 75.6 km/h maximum speed. The calculation result show that the value of energy consumption of electric bus for one cycle of Trans Jogja bus line 3A based on basic scenario, security scenario, and mitigation scenario are 82.74 kWh, 82.55 kWh, and 77.63 kWh. While ICE bus energy consumption is 88.45 kWh. CO2 emission of electric bus based on basic scenario, security scenario, and mitigation scenario are 22.59 kgCO2, 21.46 kgCO2, and 16.85 kgCO2. While CO2 emission for ICE bus is 23.60 kgCO2. In order to fulfill 6 cycles in a day operation it needs Fast DC Charging 100 kW. Keywordsâ electric bus, ICE bus, driving cycle, energy